Postpartum Contraceptive use and Rapid Repeat Pregnancy Among Women who use Substances - Loree, Amy M. (Subst Use Misuse, 2017)
BACKGROUND: Postpartum contraception is especially important for women who use alcohol and other substances, given the risk of possible rapid repeat pregnancy and prenatal substance exposure. However, little is known about postpartum contraceptive use among women with substance use histories. OBJECTIVE: To characterize postpartum contraceptive initiation, 24-month continuation, and rapid repeat pregnancy among women who used substances during pregnancy. METHODS: This is a secondary analysis of 161 pregnant women who enrolled in a randomized clinical trial to treat substance use in pregnancy and completed at least one follow-up assessment. Women were eligible if they were less than 28 weeks gestation and reported alcohol or illicit drug use within the past 30 days. Participants were recruited from two hospital-based OB/GYN clinics between 2006 and 2010, and completed assessments at delivery and 3-, 12-, and 24-months postpartum. RESULTS: Past 30-day use of any substance (not including tobacco) was 52.4%, 58.3%, and 59.8% at 3-, 12-, and 24-month follow-up, respectively. Marijuana was the most commonly reported illicit substance (as high as 48.1%). Rates of any contraceptive use were 71.3%, 66.7% and 65.3% at 3-, 12-, and 24-month follow-up, respectively; DepoProvera and condoms were the most common methods. Rapid repeat pregnancy occurred in 28% of participants by 24-month follow-up. CONCLUSIONS/IMPORTANCE: Postpartum contraceptive use among substance using women was at or near 70%, which is comparable to other samples of postpartum women. Innovative efforts are needed to promote effective contraceptive use among postpartum women in general and among those who use substances in particular.